Economic growth and urban metamorphosis: A quarter century of transformations within the metropolitan area of Bucharest - Tosa, Cristian; Mitrea, Andrei; Sato, Hitomi; Miwa, Tomio; Morikawa, Takayuki (Journal of Transport and Land Use, 2018)
This paper concentrates explicitly on examining the structural and functional transformations occurring within the metropolitan area of Bucharest, resulting from sustained economic growth during the past quarter century, by conducting a time analysis, spanning the entire period since the fall of the communist regime in late 1989. Cities in developed countries of Western Europe and Asia experienced rapid economic growth during the second half of the 20th century and exhibited novel patterns of evolution in terms of urban form and associated functional characteristics. Lately, these patterns have become manifest in Bucharest as well. However, transformations in human, social, residential, and transportation supply capital are difficult to observe directly. Hence, our methodology concentrates on studying interactions between several proxies connected to economic development within the metropolitan area of Bucharest. This paper should be read as an exploratory study that buttresses the assumption that improved economic well-being, when accompanied by the transition between a centrally planned economy to a market economy, increases motorization rates, while at the same time triggering a sharp decline in the use of public transport and contributing to aggressive urban sprawl processes. Moreover, hopefully it will guide future research dedicated to forecasting urban expansion paths and their determinants. Hopefully, it also informs policy design intended to promote sustainable urban mobility and accessibility.